Le retour des hommes sur la scène méditerranéenne - Jean-Robert Henry (Revue des Mondes Musulmans et de la Méditerranée)
Absent for a long time from the institutions which try to give shape to the relationship between Europe and its south, the human dimension of Mediterranean relations returned to agenda thanks to the determination of the “illegal” migrants. Coming from Maghreb or sub-Saharan region, they established themselves as new actors of the regional game and showed to the European and national decision-makers the illusion of a closing of human borders of Europe. The necessity to go back to a free circulation of the persons and to take Mediterranean sea as a common human space, on the European model, is a claim formulated by more and more significant representatives of the society, as manifests the very clear advice of the euro-Mediterranean civil Forum of Marrakech in November 2006.This question is now reaching the European authorities, which put on agenda for 2007 a reflexion on the new migratory policy of Europe. In reality, the question jostles European plan itself and its relation to the outside world by making it necessary to chose between a model of the European fortress and the universalist utopia of a « Europe without shores ».